1993
DOI: 10.1130/spe284-p235
|View full text |Cite
|
Sign up to set email alerts
|

Beach sands of Elba Island, Tuscany, Italy: Roundness study and evidence of provenance

Abstract: We studied the composition and roundness of medium sand from 18 small beaches of Elba Island. Six are pocket beaches less than 100 m long; the longest is 1.3 km long. The drainage basins of streams that supply the beaches are all less than 25 km 2 ; most are less than 5 km 2 . Beach sands range widely in composition owing to diverse source terrane.For the various drainage basins, comparison of the outcrop areas of the different types of bedrock with the compositions of beach sand grains yields the following co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…No textural and mineralogical maturation trends were observed in the fluvial environments along the sediment routes; instead, the grain shape parameters show overall stable values for the samples in different positions of rivers (Figure 2). These observations confirm that fluvial processes have limited effects on modifying the grain shape, as stated in previous studies (e.g., Garzanti, 2017; Picard et al., 1993; Resentini et al., 2018). However, the sand from dune fields shows significantly higher maturity in terms of geochemical and textural features (Figures 2 and 4), elucidating the sharp contrast of modification effects on sand grains between fluvial and eolian processes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No textural and mineralogical maturation trends were observed in the fluvial environments along the sediment routes; instead, the grain shape parameters show overall stable values for the samples in different positions of rivers (Figure 2). These observations confirm that fluvial processes have limited effects on modifying the grain shape, as stated in previous studies (e.g., Garzanti, 2017; Picard et al., 1993; Resentini et al., 2018). However, the sand from dune fields shows significantly higher maturity in terms of geochemical and textural features (Figures 2 and 4), elucidating the sharp contrast of modification effects on sand grains between fluvial and eolian processes.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, detrital sediments can carry valuable information concerning past geological conditions in paleoenvironment reconstructions (Folk, 1980). The sedimentological features of detrital sediments, including grain size, shape, and surface microtextures, are critical diagnostic parameters for inferring the sediment depositional environment, transport history, and associated surface processes (Boggs, 2012; Folk, 1951, 1980; Krumbein, 1941b; Picard et al., 1993). In addition, the geochemical signatures carried by detrital sediments can be used to identify the provenance, weathering intensity, and related climate they have experienced (Basu, 2017; Dutta et al., 1993; Liang et al., 2022; Muhs, 2004; Pye & Mazzullo, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The roundness of the beach sand is largely controlled by the source sediment added to the beach (Picard & McBride, ; Resentini, Andò, & Garzanti, ). Associated coastal dunes can have an increased degree of roundness compared to the source beach sand based on selective transport (Reineck & Singh, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that quartz enrichment can be due to a combination of factors. These include: (i) the composition of the source area (Basu, 1976; Mack, 1981; Picard & McBride, 1993; Nesbitt et al. , 1996; Youngson & Craw, 1996), (ii) relief (Johnsson & Stallard, 1989), (iii) extensive chemical weathering (Franzinelli & Potter, 1983; Suttner & Dutta, 1986; Corcoran et al.…”
Section: Introductionmentioning
confidence: 99%